Marangoni convection effects on heat transfer enhancement in MHD nanofluid flow over an inclined disk using magnetite and silicon nanoparticles with ethylene glycol as base fluid - Rehman, Ali; İnç, Mustafa; Jawo, Edrisa; Sudarmozhi, K. (Elsevier, 2025)
This article examines the flow of magnetohydrodynamic (MHD) nanofluids augmented by Marangoni convection (MC) over an infinite rotating inclined disk. The integration of the impacts of magnetic fields, MC, and hybrid nanofluids (HNF), utilising magnetite and silicon nanoparticles with ethylene glycol as the base fluid, on convection, flow, and heat transfer is the focus. The author employs the Homotopy analysis method (HAM), a recent approach to solving the nonlinear governing equations of the flow of a HNF, which incorporates magnetic and thermal surface tension forces. Numerically, the research demonstrates the impact of the Lorentz force, created by an increase in magnetic field strength, which in turn reduces the fluid's flow. On the contrary, the increase in the volume fractions of the nanoparticles slows the flow even further but promotes heat transfer. Even so, the MC parameter increases flow and surface temperature gradients, thereby increasing heat transfer rates. The Nusselt numbers increase as well. The residual error tables demonstrate the strong convergence of the HAM solutions, providing strong evidence of the accuracy of the developed models. Validation involves qualitative comparison with experimental and numerical studies on MHD nanofluid flows and MC. Optimization of HNF properties and the use of magnetics permits better control of flow and energy efficiency, making thermal management on turbines, electronic cooling, and solar heating systems plausible in real-time applications.
Keywords: Inclined disk; Magnetic field parameter; Homotopy analysis method; Marangoni convection; Inclined angle